Radiological imaging of the urogenital system - Nordio, E. G.; Tumanskaya, N. V.; Kichangina, T. M.; Myagkov, S. A.; Нордіо, Олена Геннадіївна; Туманська, Наталя Валеріївна; Кічангіна, Тетяна Михайлівна; Мягков, Станіслав Олександрович (Запорізький державний медичний університет, 2019)
The manual provides the basics of radiological diagnostics (investigationss, principles for obtaining images, indications for the application of these methods, and radiation signs of the urogenital system pathology) for the independent preparation of students of the third year of the International Medical Faculty.